Exploring sustainable urbanism in masterplanned developments: a collective case study of slippage between principles, policies, and practices. Issue Volume 14:Issues 1(2021) (2nd January 2021) - Parham, Susan; Jones, Alasdair
ABSTRACT: This article is concerned with masterplan implementation and with exploring, via recourse to case studies, slippages between masterplanning principles, policies, and practices. Framed by a growing body of sustainable urbanism literature we analyse evidence from five masterplanned communities in the UK and Australia to comparatively explore how some key theoretical principles are translated into placemaking in inner urban, suburban, outer urban and semi-rural contexts. We observe varying degrees of disjuncture between masterplanning principles and the urban form envisioned by, and realized through, actual masterplanning proposals and implementation. We postulate that various degrees of slippage at each stage from proposals to practices have occurred which can affect capacity to meet principles of sustainable urbanism. Analysis of the five cases demonstrates where some potential "tripping-up" points lie in the masterplanning process, hinting at broader impediments to delivering masterplanning that is more closely aligned to sustainable urbanism principles in future.